2012
DOI: 10.1111/j.1365-2230.2012.04386.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing skin ageing in a Mediterranean population from Turkey

Abstract: In this study, older age, male gender, low BMI, smoking and chronic sun exposure had a negative influence on skin ageing in a Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
4
20
2
Order By: Relevance
“…Perhaps, it was due to the smaller sample size. Contrary to Ekiz et al's study that showed significantly higher WS in patients with higher BMI, no significant relation was found between BMI and facial aging in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Perhaps, it was due to the smaller sample size. Contrary to Ekiz et al's study that showed significantly higher WS in patients with higher BMI, no significant relation was found between BMI and facial aging in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Various studies on the influence of personal habits and behaviors (sunlight exposure, cigarette smoking, alcohol and coffee consumption, and cleaning teeth) on facial wrinkles show discrepancies in results . In the present study, exposure to the sunlight had a significant association with wrinkling score.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In our study 47.1% of the patients were smokers. In a study performed in Ankara, smoking incidence was found as 27% in 574 individuals . The high prevalence of smoking in our study and the Takci et al .…”
Section: Discussionsupporting
confidence: 67%
“…Despite ongoing efforts to educate the general public on immediate and delayed UV-related health risks including sunburn, alteration of the immune system, photoaging, ocular disorders and skin cancer, sunbathing in leisure time, outdoor activities with insufficiently protected skin and tanning parlour use are still widely accustomed in Western countries [4,5]. In synopsis with scientific research reporting that major motivating factors for having a tanned skin are appearance-related (e.g., the perceived attractiveness of a suntanned skin), sunbathers may belief that their individual advantages of UV light exposure outweigh the well-known disadvantages [6][7][8].…”
Section: Introductionmentioning
confidence: 99%